Protection and obedience. Deviant masonry, corruption, and mafia in Italy - Sergi, Anna (Deviant behavior, 2023)
The historical connection between Italian masonry and opaque interests of white-collar and institutional actors populates common representations of power in Italy. The P2 case contributed to shape an Italian collective representation of the role of the masonry as a locus where almost everything can be informally or illegally obtained by affiliates through the right connections, bribery, and blackmailing. Using a variety of resources, including case law, public inquiries, interviews, and media analysis, this paper will investigate the pathological dimension of potential interplays among deviant masons and political-institutional actors in a variety of cases from the P2 onwards. Marginally mafia organizations have also emerged in this interplay. We outline the actors, their resources, activities, and opportunities. We conclude by discussing how and why the willingness and the need of several powerful actors (including mafiosi) to find a "protected space" of extra-legal exchange, led them to create, seek, or enter masonic or para-masonic structures, able to provide governance of reciprocal needs and expectations.